Anti-Diarrheal Activity of Aqueous Extract Datura Innoxia Leaves in Rat - Farrah R. Jaafar (Journal of Global Pharma Technology, 2018)
Two experiments were performed, to study the therapeutic effect DI leaf extract against chemically induced diarrhea as well as anti-enter pooling effect induced by castor oil in two gatherings (T1&T2) Treated orally with (Datura innoxia leaves aqueous) extract at doses of 100 and 200 mg/Kg B.W. and compared with atropine sulphate treated group as standard drug and control one, each group consist of 6 albino rat. Exp-The results show significant decrease (P<0.05) in charcoal Intestinal travelling percent (ITP)in both DI extract doses in dose dependent manner T2 when compared to of atropine sulphate (1mg/kg BW) show similar result. While Ex-2 Nearly same patter results as in exp-1in which both orally treated DI extract doses and atropine(3mg/Kg BW) caused significant reduction (P˂0.05) in(enter pooling impact) on intestinal substance weight and volume in examination with the control gathering. The possibly because the DI extract may have another impact component next ant muscarinic impact cause its tropane alkaloids content. Inclusion, DI leaves aqueous seem to cause anti-diarrheal effect and intestinal anti-propulsion effect positive correlated with extract dose.Keywords: Aqueous extract, datura innoxia leaves, Anti-diarrheal Activity, Enteropooling, Rat.